Valistunut ymmärrys : Robert Alan Dahlin demokratiateoria politiikkatietämyksen valossa - Tiitto, Niko Kristian (2019)
Democratic theorists have generally agreed on that citizens should possess some minimal amount of politically relevant knowledge if democracy, however envisioned, is to work. What the actual standard of such politically relevant knowledge ought to be is, however, under debate. While such debates reflect controversies in the meaning and purpose of democracy in normative democratic theory, empirical studies have made strides in assessing the level of actual political knowledge – the amount of factual political information possessed – of citizens. While earlier studies painted a dim picture of the general citizenry’s level of political knowledge, current empirical studies have shown that political knowledge is distributed surprisingly equally among the populace, with most citizens possessing at least an adequate level of political knowledge. The extremes of the politically well-informed and the politically uninformed, however, do exist. These empirical findings are important for democratic theorizing because political knowledge affects political participation, perhaps one of the main issues in normative democratic theory. However, while empirical studies have furthered our understanding of the actual level of political knowledge as well as its effects to political behaviour, normative democratic theory rarely resorts to empirical evidence as construed by empirical political scientists. This leads to undertheorizing and missed opportunities in synthesizing empirical and normative findings for the purpose of advancing democratic thought and innovations. In my thesis I study Robert Alan Dahl’s democratic theory in the light of empirical evidence about political knowledge. I try to answer two questions: “What should citizens really know about politics according to Dahl?” and “How such knowledge about politics could be measured?” I review Dahl’s democratic theory and use his ideas relevant to questions about citizen competence and political knowledge as potential sources for operationalization and measurement. I found that Dahl’s theorization on citizen knowledge and political competence were underdeveloped but could be potentially tied to current research on political knowledge. I also propose that Dahl’s normative theory could be used as a guideline for future research in political knowledge and in democratic innovations. Key words: democratic theory, enlightened understanding, political knowledge, political sophistication, Robert Alan Dahl